2020
DOI: 10.1155/2020/7953289
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Preeclampsia on Hematological Profile of Newborns in Qatar

Abstract: Background. Preeclampsia is a major cause of pregnancy-related maternal, fetal, and neonatal morbidities and mortalities. We aimed to review the effect of maternal preeclampsia on the hematological profile of newborns in the Qatari population. Methods. In this case-control study, we reviewed data and complete blood count results of neonates born to Qatari women diagnosed of preeclampsia in 2017 in comparison with data of a control group. Statistical analysis was done using unpaired t-test, chi-square test, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
(11 reference statements)
0
6
1
Order By: Relevance
“…However, these authors did not report on the degree of thrombocytopenia, which is considered mild (150,000 to 100,000), moderate (100,000 to 50,000), and severe (< 50,000) according to the platelet count 10,11 . Conversely, Bayoumi et al reported thrombocytopenia degrees: mild in 13% of neonates born to mothers with PIH compared to 2% in the control group 13 . Tsao et al also estimated a 36% incidence of mild thrombocytopenia in neonates with the same condition 9 .…”
Section: Discussionmentioning
confidence: 91%
“…However, these authors did not report on the degree of thrombocytopenia, which is considered mild (150,000 to 100,000), moderate (100,000 to 50,000), and severe (< 50,000) according to the platelet count 10,11 . Conversely, Bayoumi et al reported thrombocytopenia degrees: mild in 13% of neonates born to mothers with PIH compared to 2% in the control group 13 . Tsao et al also estimated a 36% incidence of mild thrombocytopenia in neonates with the same condition 9 .…”
Section: Discussionmentioning
confidence: 91%
“…There is intense interest in the search for biochemical indexes that are related to hematological parameters, including the neutrophil-lymphocyte ratio, red cell distribution width, and platelet parameters, which are simple procedures and easily obtainable (17,18). Platelet parameters have been found to exhibit change before the onset of PE, and several researchers have implied that they can be used in the second trimester as useful biochemical markers for the prediction of PE (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Gestational hypertension and preeclampsia may have similar pathophysiological processes 12,13 . The incidence of early-onset thrombocytopenia in neonates born to mothers with preeclampsia is approximately 9.2-36%, which is significantly higher than that in newborns of normotensive mothers 4,9,14,15 . Therefore, we hypothesized that maternal gestational hypertension impacts the incidence of early-onset neonatal thrombocytopenia.…”
Section: Introductionmentioning
confidence: 91%